The role of small pelagic fish in diverse ecosystems: knowledge gleaned from food-web models - Ruzicka, James (2024)
Small pelagic fish (SPF) are important forage species and a target of major fisheries within diverse ecosystems. SPF are a critical link between plankton and higher trophic levels. Understanding the network of dependencies among species and fisheries supported by SPF is required for effective resource management and assessment of risks posed by environmental and anthropogenic stressors. Food-web models represent a synthesis of knowledge of these dependencies and are a platform for evaluating the consequences of change in SPF productivity. From Ecopath food-web models archived within EcoBase (www.ecobase.ecopath.org) and from peer-reviewed literature, we compiled physiological parameters, biomasses, diets, and fishery catch rates that define SPF characteristics. From 199 models, metrics characterizing demand on ecosystem production, contribution to predators and fisheries, and sensitivities to changes in SPF were calculated. Across all models, globally, SPF represented 43% of total fish production and were supported by 8% of total primary production (14% in open ocean and 10% in upwelling models). In turn, SPF represented 18% of total fish and invertebrate catch (53% in upwelling models). From a services perspective, considering all direct and indirect trophic pathways, SPF were major contributors to predators and fisheries. On average, SPF supported 22% of seabird production, 15% of mammal production, and 34% of total fisheries catch. Support to upper trophic levels was greater in upwelling models (33% of seabird, 41% of mammal, and 62% of fishery production). These analyses show the importance of accounting for direct and indirect support by SPF to predators and fisheries when making management decisions.